Understanding Plant Nutrition-The Genesis of Students' Conceptions and the Implications for Teaching Photosynthesis - Denis Messig; Jorge Groß (MDPI AG, 2018)
Plant nutrition and photosynthesis is one of the most difficult issues teachers are confronted with in science classes. This can be due to alternative conceptions students’ hold, which are often profoundly contrary to their scientific counterparts. Consequently, fruitful learning environments should build on learners’ alternative conceptions to initiate conceptual change towards a more scientific understanding. In this qualitative case study, high-school students’ pre-instructional conceptions about plant nutrition were identified empirically. Afterwards these students were exposed to the van-Helmont experiment in order to create a cognitive conflict. The learning processes and signs of conceptual change were identified using Qualitative Content Analysis. The results show that the van-Helmont experiment does not trigger conceptual change but reinforces students’ pre-instructional conceptions. Ultimately, a cognitive-linguistic analysis using Conceptual Metaphor Theory was conducted. Interestingly, underlying embodied conceptions and image schemas about human nutrition became evident. These thinking patterns were used metaphorically and, therefore, can be seen as the basis to understand plant nutrition. As a result, we propose a reverse approach of teaching photosynthesis and nutrition. Our Dissimilation-Before-Assimilation approach takes learners’ alternative conceptions and underlying image schemas into account in order to promote a fruitful learning of the concepts of plant nutrition.